2022
DOI: 10.3389/fpsyg.2022.816587
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Concerns in Patients With Head and Neck Cancer: A Longitudinal Study

Abstract: ObjectiveHead and neck cancer (HNC) treatments are known to significantly affect functionality and appearance, leading to an increased risk for body image disturbances. Yet, few longitudinal studies exist to examine body image in these patients. Based on a conceptual model, the current study aimed to determine, in patients newly diagnosed with HNC: (1) the prevalence, level, and course of body image concerns; (2) correlates of upon cancer diagnosis (pre-treatment) body image concerns; (3) predictors of immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 77 publications
4
29
0
Order By: Relevance
“…Radical surgery was found in previous studies to change one’s appearance and have an impact on body image concerns [ 13 ]. Physical functioning as a determinant is also in accordance with past research, which found impairments in speech and eating as predictors of body image concerns [ 6 , 31 , 32 ]. Having a positive body image often means placing less value on physical appearance and more on physical ability and functionality [ 6 , 20 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Radical surgery was found in previous studies to change one’s appearance and have an impact on body image concerns [ 13 ]. Physical functioning as a determinant is also in accordance with past research, which found impairments in speech and eating as predictors of body image concerns [ 6 , 31 , 32 ]. Having a positive body image often means placing less value on physical appearance and more on physical ability and functionality [ 6 , 20 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Physical functioning as a determinant is also in accordance with past research, which found impairments in speech and eating as predictors of body image concerns [ 6 , 31 , 32 ]. Having a positive body image often means placing less value on physical appearance and more on physical ability and functionality [ 6 , 20 , 33 ]. Patients who are less physically able because of pain or other symptoms can experience an altered perception of their bodies [ 6 , 20 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations